EDUCATIONAL IDEAS OF MARIA MONTESSORI ON THE PAGES OF FOREIGN PERIODICALS - Alla Durdas (Borys Grinchenko Kyiv Metropolitan University, 2023)
The article deals with the educational ideas the famous Italian doctor and educator Maria Montessori, her many-sided personality, some aspects of the life, activities and methods highlighted on the pages of foreign periodicals. The relevance of the pedagogue's ideas in the modern world has been stressed; the demand of the modern society for the education of a free individual, striving for independent active searches and self-realization, has been emphasized. The article reveals the personality of M. Montessori as one of the educators who was able to pose and solve a global problem in philosophical, psychological and pedagogical theory, as well as to implement her concept in practice, creating a pedagogical system named as «Montessori method». M. Montessori; as an educator who gave a new quality to the education development strategy, humanizing it, returning it to the person. The analysis of M. Montessori's pedagogical activities, positions, views and her life paths, highlighted by foreign researches, have been presented in the article; her role as an architect of the «rediscovery» of the child has been stressed. The educator's revolutionary ideas about childhood and education for life, rather than education based on obedience and immobility, have been noted as well as their development as a result of M. Montessori's medical research has been admitted; her new visions of the school by designing strategies that would overcame the barriers to education, have been mentioned. The article also stresses the educator's desire to show how to save humanity by means of pedagogy: starting with the child and human freedom and, in particular, freedom for women.